Development of Web-Enabled Online Learning Effectiveness Model Based on Online Video Tutorial - Bramantiyo Eko Putro; Rajesri Govindaraju (Jurnal Ilmiah Teknik Industri, 2021)
Information technology has a major impact on knowledge-sharing activities. The combination of knowledge-sharing tools such as Web 2.0 and multimedia embodied in the use of tutorial videos on web-enabled online learning is the solution. The solution is expected to improve individual performance in solving troubleshooting problems. The model was developed which explained the relationship between knowledge sharing and individual performance in troubleshooting problems and identified the factors that influence it. The research data is obtained by distributing questionnaires online to Telkomsel service users who have experienced problems troubleshooting products or services. The conceptual model was tested based on 205 samples obtained online. From the test results, it can be seen that web-enabled online learning is effective because tacit knowledge sharing that occurs directly increases individual performance while the effect of explicit knowledge sharing is mediated by tacit knowledge sharing. The factors that drive knowledge-sharing activities can influence individual performance, namely trust, IT usage, and usability.